Tradisi Tepung Tawar: Integrasi Agama dan Kebudayaan pada Masyarakat Melayu di Sumatera Utara - Taslim Batubara; Badrun Badrun; Ahmad Muhajir (Medan Resource Center, 2022)
This article discusses the tradition of fresh flour which is still practiced by ethnic Malays in North Sumatra in various traditional ceremonies that are considered sacred. In this article the author uses the historical method. The historical method according to Gottschalk (1986) is a process of critically examining and analyzing records of past relics. Imaginative reconstruction of the past based on data obtained by going through that process is called historiography. The results showed that this tradition of plain flour had been practiced and was influenced by beliefs before the arrival of Islam to the North Sumatra region. Fresh flour comes from the word tampung Tawar which means the activity of accepting bidders by being accommodated (to hold hands) as a form of receiving bidders (drugs) and has a magical function. This tradition is also a means of asking God for blessings and privileges, so that all good things are poured out for people who are offered flour and kept away from bad things in their lives. In addition, this tradition is also a symbol of integration between religion and culture, especially in the North Sumatra region.